Managing in-play run chases in limited overs cricket using optimized CUSUM charts - Bose, D.; Chakraborty, S. (Journal of Sports Analytics, 2019)
In this paper, we present the application of CUSUM control charts to analyze the outcome of a limited overs cricket match during the second innings. This approach makes use of the target set in the first innings and the runs scored from each ball in the second innings. We have analyzed the ball-by-ball data of 1180 One Day Internationals and 537 T20 Internationals played between 2006 and 2017. To improve the accuracy of our models, we have applied genetic algorithm to generate optimal control chart parameters that maximize the accuracy of the model outcome. Our analyses are found to be correct in 80-89% of ODI matches and 76-84% of T20 matches, depending on the stage of in-play analysis.